I being the intercenter of the triangle means that IA = BI= CI
CI = 52-2X
AI = 3X +7 ==> AI = IC ==> 3X+7 = 52-2X SOLVE FOR X
3X+2X = 52-7 ==> 5X = 45 & X =9
IF X = 9 THEN IC = 52-2(9) = 34. IC =34
56.57
Explanation:
In the process,
Diameter= 18,
Radius(r)=
18
2
∴
Radius= 9
Now,
Circumference (Perimeter) = ?
According to the formula,
Perimeter= 2
×
22
7
×
r
Taking the equation,
Perimeter= 2
×
22
7
×
r
2
×
22
7
×
9
396
7
56.57142857
56.57
Let's hope this helps you:)
Answer:
1
Step-by-step explanation:
Simplifying
3x + 2(4x + -4) = 3
Reorder the terms:
3x + 2(-4 + 4x) = 3
3x + (-4 * 2 + 4x * 2) = 3
3x + (-8 + 8x) = 3
Reorder the terms:
-8 + 3x + 8x = 3
Combine like terms: 3x + 8x = 11x
-8 + 11x = 3
Solving
-8 + 11x = 3
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 8 + 11x = 3 + 8
Combine like terms: -8 + 8 = 0
0 + 11x = 3 + 8
11x = 3 + 8
Combine like terms: 3 + 8 = 11
11x = 11
Divide each side by '11'.
x = 1
Simplifying
x = 1
Answer:
Ok:
Step-by-step explanation:
So f°g . means f(g(x)). (The ° should be more center and bigger but I don't know to do that on a keyboard). f(g(x)) means that you replace the x in f(x) with the g(x) function. i.e:
if f(x) = 2x+2
and g(x) = ![x^2](https://tex.z-dn.net/?f=x%5E2)
f(g(x)) =
.
Similarly, in this case, we get f(x) = 2x-3 and g(x) = 3x-2.
Then, f(g(x)) or f°g(x) is 2(3x-2) - 3.
And we plug in -2 to solve:
2(3(-2)-2)-3.
and get -19.
Check if I am wrong because everyone makes mistakes but that is the way to solve this.
Answer:
HL
Step-by-step explanation: